GE_GERICHTE A/3989/2005 vom 1. März 2006 - GE Cour de justice (2006)
; AI(ASSURANCE) ; RÉVISION(PRESTATION D'ASSURANCE) ; RÉVISION(DÉCISION) ; EFFET SUSPENSIF DU RECOURS ; EFFET SUSPENSIF(MESURE PROVISIONNELLE) ; MESURE PROVISIONNELLE ; RENTE D'INVALIDITÉ ; PROCÉDURE ; PROCÉDURE ADMINISTRATIVE | PA55; PA56